THE INFLUENCE OF INSULIN RESISTANCE ON THERAPEUTIC RESPONSE IN NEWLY DIAGNOSED PATIENTS WITH MULTIPLE MYELOMA - Vlaisavljević, Nada; Urošević, Ivana; Tomić Naglić, Tomić Naglić (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: According to the results of previous research, it was found that the dysfunction of the insulin-like growth factor (IGF) system, which is the basis of insulin resistance with hyperinsulinemia, acts as a proliferative tumor factor, and its neoplastic potential is also exhibited in multiple myeloma.Study aim: The study aims to determine whether there is an association between insulin resistance in patients newly diagnosed with multiple myeloma (NDMM) and the achieved therapeutic response after induction chemotherapy.Materials and methods: The prospective study included 35 NDMM patients (60% women and 40% men), treated at the Clinical Center of Vojvodina Clinic for Hematology. Glycemia and insulinemia levels were determined after fasting and postprandially, upon which the values of HOMA-IRIf (after fasting) and HOMA-IRIpp (postprandially) were calculated. HOMA-IRI values > 2.2 were the criteria for insulin resistance. The analyses were performed twice – before the initial chemotherapy and after the completion of the treatment. The therapeutic response was evaluated according to the criteria of the Serbian Myeloma Group (SMG) and the International Myeloma Working Group IMWG). Statistical analyses were performed in the SPSS program, Version 22.Results: The average patient age was 63.85 years. In total, 86% of patients responded favorably to the therapy. The average value of HOMA-IRIf before treatment was 1.82 ± 0.79 and it was 1.80 ± 0.72 after therapy. The central median value of HOMA-IRIpp before treatment was 5.46, with an interquartile range of 1.07 – 20.57, and after treatment, it was 5.86 with an interquartile range of 1.22 – 28.22. A significant negative correlation between HOMA-IRIf after applied treatment and achieved therapeutic response was observed, (p = 0.040).Conclusion: Active concomitant therapy of insulin resistance in NDMM could improve the response to applied antimyeloma treatment.
Keywords: hyperinsulinemia; multiple myeloma; therapeutic response